Religion in the Age of Development - Feener, R. Michael (Religions, 2018)
Religion has been profoundly reconfigured in the age of development. Over the past half century, we can trace broad transformations in the understandings and experiences of religion across traditions in communities in many parts of the world. In this paper, we delineate some of the specific ways in which religion' and development' interact and mutually inform each other with reference to case studies from Buddhist Thailand and Muslim Indonesia. These non-Christian cases from traditions outside contexts of major western nations provide windows on a complex, global history that considerably complicates what have come to be established narratives privileging the agency of major institutional players in the United States and the United Kingdom. In this way we seek to move discussions toward more conceptual and comparative reflections that can facilitate better understandings of the implications of contemporary entanglements of religion and development.